Kinematic and dynamic analyses of the front crawl tumble turn in elite female swimmers - Puel, F.; Morlier, J.; Pyne, D.; Hellard, P. (Sports Biomechanics, 2022)
Based on a three-dimensional (3D) underwater analysis, the objective of the present study was to identify the biomechanical variables the most associated with turn times in 10 elite female swimmers. For each participant (95.7 ± 2.6% of the 200 m freestyle world record), the best-time turn (from 3 m in to 3 m out, 2.89 ± 0.08 s) was analysed from a three-dimensional (3D) direct linear transformation kinematical reconstruction and the use of a piezoelectric force platform. Bivariate analysis showed that lateral impulse was linked to turn time (r = -0.76, p = 0.01) as well as horizontal velocities at end of the glide and swim resumption (respectively, 1.88 ± 0.2 m·s-1 and 1.48 ± 0.15 m·s-1; r = -0.67 and -0.68; p < 0.05 for both variables). One variable was considered relevant in the best Lasso (Least Absolute Shrinkage and Selection Operator) model: the lateral impulse (8.8 ± 5.1 N·s) during the placement sub-phase.The best tumble turn times were associated with higher lateral impulse during the placement and faster velocities during the underwater actions. The lateral impulse may reflect the swimmers` longitudinal rotation which was higher for the fastest swimmers.